PENGARUHPEMBELAJARAN GROUP INVESTIGATIONTERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK SMP - Anisa Safitri (Jurnal Edukasi dan Penelitian Matematika, 2018)
Mathematical problem solving ability is one of abilities that is expected to develop optimally forlearners. But, based on the result from observation showed that mathematical problem solving ability of students in a SMPNegeri1 Padanggrade VIIIdid not developed optimally yet. One of the efforts to apply Group Investigation model.Type of this research is quasi-exsperiment with static grup design with simple random sampling. According to the research result, we can conclude that mathematical problemsolving ability of learners who follow Group Investigation model learning is better than the mathematical problem-solving ability of learners who follow conventional learningwith a significance level of 0,05.  Keywords –Group Investigation, mathematical problem solving ability, conventional learning.